Myopia-attributable economic burden in Japan: a cost-of-illness modelling study with probabilistic sensitivity analysis and projection to 2050 - Ryo Kubota (Journal of Global Health Economics and Policy, 2026)
Background Myopia is a major global public health concern, with about half the world’s population projected to be myopic by 2050. Cost-of-illness work in urban China indicates that the economic burden of myopia is dominated by lost productivity rather than by treatment cost. Japan has a high adult myopia prevalence and a rapidly ageing, contracting workforce, but no myopia-specific economic estimate exists. We aimed to produce an exploratory estimate of the annual myopia-attributable economic burden in Japan and to project it to 2050. Methods We conducted an exploratory prevalence-based cost-of-illness modelling study from a societal perspective, in Japanese yen (JPY) at 2024-2025 price levels, with United States dollar (USD) equivalents at 150 JPY per USD. The deterministic base case combined Japanese myopia prevalence with published international productivity-loss parameters and Japanese wage and labour statistics. A Monte Carlo probabilistic sensitivity analysis (PSA) of 10 000 iterations jointly varied all uncertain parameters across pre-specified probability distributions. Estimates were compared with the published all-cause visual impairment burden for Japan and with the East Asia productivity-loss estimate. Results The deterministic base case was JPY 4.3 trillion (USD 28.5 billion) per year, equal to 0.64% of gross domestic product. The PSA gave a median annual burden of JPY 4.0 trillion (USD 26.4 billion), with a 95% credible interval (CrI) of JPY 1.7-8.3 trillion (USD 11.4-55.6 billion) and an interquartile range of JPY 3.0-5.2 trillion (USD 19.9-34.6 billion). A narrower scenario-based range, obtained by varying only the productivity decrement across its plausible bounds of 1-3% while holding other parameters at base values, gave JPY 2.6-5.9 trillion (USD 17.4-39.5 billion). Lost productivity accounted for a mean of 77% of the total. The estimate was dominated by a single uncertain parameter, the assumed mild-to-moderate productivity decrement (Spearman rho=0.97), reflecting the absence of Japanese empirical data on this quantity. Scenario projection gave JPY 5.0-10.7 trillion (USD 33.2-71.1 billion) by 2050. Conclusions Under plausible parameter ranges the myopia-attributable economic burden in Japan appears non-trivial and productivity-dominated, but the wide credible interval shows that its magnitude cannot be quantified precisely without Japanese productivity research. The estimate should be read as an exploratory modelling exercise intended to motivate empirical work, not as a definitive national accounting.